The Heritage of Toraja Cultural Values in the Academic Context of a Higher Education in Toraja - Oktavianus Pasoloran; Markus Deli Girik Allo; Perdy Karuru; Theresyam Kabanga'; Daud Kaluring (STAI Hubbulwathan Duri, 2024)
The purpose of this study is to investigate how the implementation of the inheritance of Tongkonan Values in the academic context of UKI Toraja. This research uses a qualitative approach using a case study method that focuses on a university, namely the Indonesian Christian University of Toraja. The informants in this study were elements of the Toraja Church Synod Workers Board, Makale Christian College Foundation Board, University Management and UKI Toraja academic community, and Toraja community leaders. This research data was obtained through observation instruments and interviews. The data analysis technique used is thematic analysis through coding of interview transcripts or observation note. This study confirms that as a vibrant centre for social and intellectual activities, UKI Toraja is a vital hub for fostering community bonds, and as a community development centre, it plays a crucial role in driving positive change and contributing to the overall advancement of the Torajan community, exemplifying a holistic approach to societal well-being that preserves traditions while embracing progressive change.